High-flow nasal oxygen therapy alone or with non-invasive ventilation in immunocompromised patients admitted to ICU for acute hypoxemic respiratory failure: the randomised multicentre controlled FLORALI-IM protocol. Issue 8 (10th August 2019) - Coudroy, Rémi; Frat, Jean-Pierre; Ehrmann, Stephan; Pène, Frédéric; Terzi, Nicolas; Decavèle, Maxens; Prat, Gwenaël; Garret, Charlotte; Contou, Damien; Bourenne, Jeremy; Gacouin, Arnaud; Girault, Christophe; et al.
Abstract : Introduction: Non-invasive ventilation (NIV) is recommended as first-line therapy in respiratory failure of critically ill immunocompromised patients as it can decrease intubation and mortality rates as compared with standard oxygen. However, its recommendation is only conditional. Indeed, the use of NIV in this setting has been challenged recently based on results of trials finding similar outcomes with or without NIV or even deleterious effects of NIV. To date, NIV has been compared with standard oxygen but not to high-flow nasal oxygen therapy (HFOT) in immunocompromised patients. Several studies have found lower mortality rates using HFOT alone than when using HFOT with NIV sessions in patients with de novo respiratory failure, and even in immunocompromised patients. We are hypothesising that HFOT alone is more effective than HFOT with NIV sessions and reduces mortality of immunocompromised patients with acute hypoxemic respiratory failure. Methods and analysis: This study is an investigator-initiated, multicentre randomised controlled trial comparing HFOT alone or with NIV in immunocompromised patients admitted to intensive care unit (ICU) for severe acute hypoxemic respiratory failure. Around 280 patients will be randomised with a 1:1 ratio in two groups. The primary outcome is the mortality rate at day 28 after inclusion. Secondary outcomes include the rate of intubation in each group, length of ICU and hospital stay and mortality up to day 180. Ethics and dissemination: The study has been approved by the ethics committee and patients will be included after informed consent. The results will be submitted for publication in peer-reviewed journals. Trial registration number: NCT02978300